WAYS OF IMPLEMENTING A COMPLEX APPROACH TO INCREASE THE COMPETITIVENESS OF UKRAINE - Alisa S. Mahdich; Oleksandr A. Zadoia; Artem M. Novikov (European Vector of Economic Development)
The study focuses on examining the key factors influencing the competitive state of Ukraine’s socio-economic model at the current stage of development. An analysis of major macroeconomic parameters on the eve of Russia’s full-scale invasion revealed substantial potential for economic recovery following the losses incurred due to COVID-19 pandemic restrictions. Taking into account recent European Union reforms aimed at enhancing competitiveness based on the European Commission’s Communication to the European Parliament, the Council, the European Economic and Social Committee, and the Committee of the Regions, titled «Long-term competitiveness of the EU: looking beyond 2030,» certain related directions for implementing relevant transformations in Ukraine have been identified. As a result, the authors developed a comprehensive approach to enhance the competitiveness of Ukraine. Correspondingly, possible pathways for implementing specific components of this comprehensive approach were proposed. It has been determined that, through incentives involving public and business influence on the elite, it is necessary to ensure the development, implementation, and monitoring of the most urgent reforms, namely: security reform, institutional reform, infrastructure reconstruction, and innovation reform. The most critical steps were identified, primarily involving the deepening of cooperation with foreign partners at both business and governmental levels. The need for decisive action against corruption in all areas of life and the urgent institutional reform required was also highlighted. Using G. Hofstede’s cultural dimensions theory, a regression analysis was conducted to explore the relationship between institutional quality ratings from the “Global Competitiveness Index” and Ukraine’s cultural dimension values. Based on these calculations and the evaluation of statistical correlation density through the determination coefficient, it was found that higher individualism correlates with higher institutional quality, while higher power distance correlates with lower institutional quality. The dependency of institutions on other cultural dimensions was too weak to indicate a meaningful relationship; however, graphical analysis of long-term orientation and uncertainty avoidance suggested a shared dynamic. Three main directions for implementing institutional reform were proposed: fostering civic patriotism among the population, combating the old, corrupt, anti-national elite (oligarchs), and cultivating patriotic meritocrats as replacements. Meeting these conditions would establish a strong foundation for further development of a rule-of-law state. Regarding infrastructure reconstruction and innovation reform, plans for modernization and digitalization were proposed. Particular attention should be paid to implementing and utilizing modern tools to leverage the full spectrum of financial and stock market opportunities. The implementation of modern educational approaches at all levels is also of great importance. The successful combination and implementation of these proposed processes will lead to increased productivity and competitiveness. The driver of positive changes should be Ukrainian business and civil society: entrepreneurs understand what is needed for dynamic growth, and citizens know what is required for a decent life.